High input impedance voltage-mode biquad filter using VD-DIBAs - Jaikla, Winai; biolek, Dalibor; siripongdee, Surapong; Bajer, Josef (My University, 2014)
This paper deals with a single-input multipleoutput biquadratic filter providing three functions (lowpass, high-pass and band-pass) based on voltage differencing differential input buffered amplifier (VD-DIBA). The quality factor and pole frequency can be electronically tuned via the bias current. The proposed circuit uses two VD-DIBAs and two grounded capacitors without any external resistors, which is suitable to further develop into an integrated circuit. Moreover, the circuit possesses high input impedance, providing easy voltage-mode cascading. It is shown that the filter structure can be easily extended to multi-input filter without any additional components, providing also all-pass and band-reject properties. The PSPICE simulation results are included, verifying the key characteristics of the proposed filter. The given results agree well with the theoretical presumptions.
Keywords: Analog filter; Single input multiple output; VD-DIBA; Voltage-mode